2023
DOI: 10.1038/s41398-023-02459-6
|View full text |Cite
|
Sign up to set email alerts
|

Depression and 24 gastrointestinal diseases: a Mendelian randomization study

Abstract: The causality of the association between depression and gastrointestinal diseases is undetermined. We conducted Mendelian randomization (MR) analyses to systematically explore the associations of depression with 24 gastrointestinal diseases. Independent genetic variants associated with depression at the genome-wide significance level were selected as instrumental variables. Genetic associations with 24 gastrointestinal diseases were obtained from the UK Biobank study, the FinnGen study, and large consortia. Mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…[ 26 ] Increasing prevalence of anxiety and depression in CP patients was observed [ 27 ] and a MR analysis revealed that genetic liability to depression was associated with an increased risk of CP. [ 28 ] Combined with our MR results, we believed that changes in the gut microbiota of CP may be partly due to its accompanying black mood or depression.…”
Section: Discussionsupporting
confidence: 56%
“…[ 26 ] Increasing prevalence of anxiety and depression in CP patients was observed [ 27 ] and a MR analysis revealed that genetic liability to depression was associated with an increased risk of CP. [ 28 ] Combined with our MR results, we believed that changes in the gut microbiota of CP may be partly due to its accompanying black mood or depression.…”
Section: Discussionsupporting
confidence: 56%
“…A total of 4,537 publications were initially recovered by database searching, of which 4,501 were excluded because of duplication or unsuitability. Finally, 36 eligible studies were included in this systematic review and meta-analysis (7–11,13,14,17,18,22–48). The workflow of the search strategy and study selection have been illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…adjusted for potential confounders with corresponding 95% confidence intervals (CI). Finally, concerning the third study outcome, we included studies that evaluated the association of genetic liability to exposure with the risk of the outcome of interest using the Mendelian randomization (MR) approach (14,17,18). The MR study is an innovative research method that explores the causal link between exposure and outcome using specific genetic markers (single-nucleotide polymorphisms) strongly correlated with exposure as instrumental variables (IV).…”
Section: Methodsmentioning
confidence: 99%
“…In the eastern region, "liver disease-metabolic disease", "liver disease- stomach disease", and "liver disease-arthritis" are important combination patterns, with the main influencing factors being sleep duration of less than 6 h, frequent drinking, female, and daily activity capability. The more developed economy in the eastern region of China may lead to insufficient sleep [ 58 , 59 ] and unhealthy habits such as frequent alcohol consumption, consumption of take-out foods [ 60 ], as well as a faster pace of life, potentially increasing the prevalence of liver disease, metabolic diseases, or stomach diseases. Additionally, the higher degree of industrialization in the eastern region may lead to more severe air pollution, potentially increasing the incidence of inflammatory diseases such as arthritis [ 61 ].…”
Section: Discussionmentioning
confidence: 99%